Polarization of Λ and ¯Λ hyperons along the beam direction in Pb-Pb collisions at √sNN=5.02 TeV$ - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Berdnikova, Anastasia; Bergmann, Luisa; Danisch, Meike; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Köhler, Markus Konrad; Kroesen, Martin; et al. (Physical review letters, 2022)
The polarization of the Λ and ¯Λ hyperons along the beam (z) direction, Pz, has been measured in Pb-Pb collisions at √sNN=5.02 TeV recorded with ALICE at the Large Hadron Collider (LHC). The main contribution to Pz comes from elliptic flow-induced vorticity and can be characterized by the second Fourier sine coefficient Pz,s2=⟨Pzsin(2φ−2Ψ2)⟩, where φ is the hyperon azimuthal emission angle and Ψ2 is the elliptic flow plane angle. We report the measurement of Pz,s2 for different collision centralities and in the 30%-50% centrality interval as a function of the hyperon transverse momentum and rapidity. The Pz,s2 is positive similarly as measured by the STAR Collaboration in Au-Au collisions at √sNN=200 GeV, with somewhat smaller amplitude in the semicentral collisions. This is the first experimental evidence of a nonzero hyperon Pz in Pb-Pb collisions at the LHC. The comparison of the measured Pz,s2 with the hydrodynamic model calculations shows sensitivity to the competing contributions from thermal and the recently found shear-induced vorticity, as well as to whether the polarization is acquired at the quark-gluon plasma or the hadronic phase.